Predicting, Identifying, and Characterizing small non-coding RNAs Implicated in Regulating Clavulanic Acid Production in Streptomyces Clavuligerus (2025)
ABSTRACT : Commercial strains of Streptomyces clavuligerus, such as ATCC 27064, produce clavulanic acid in low quantities. Increasing the production of this metabolite is essential for decreasing the cost of clavulanic acid (CA) prescriptions, thereby promoting successful treatments against resistant bacterial infections and making them accessible to poor communities. Understanding the regulatory pathways for clavulanic acid production is crucial for developing new genetically modified strains with enhanced metabolic capabilities for CA production. Recently, several studies have revealed the pivotal role of small non-coding RNAs in regulating various metabolic processes in both prokaryotic and eukaryotic organisms. However, knowledge about small RNAs (sRNAs) in Streptomyces clavuligerus is scarce. This thesis aimed to use cutting-edge bioinformatics tools and a compendium of RNA-seq data to predict the potential coding of sRNAs that might be present in the genome of Streptomyces clavuligerus ATCC 27064. In the genome of Streptomyces clavuligerus 606 intergenic regions (IGRs) are conserved, and 272 possess a highly thermodynamically stable and conserved secondary structure, indicating the presence of non-coding RNA in these regions. The transcriptome assembly of S. clavuligerus showed that the genome is completely functional, as all the annotated genes are expressed under the conditions analyzed. From this assembly, transcripts originated from IGRs were labeled as putative sRNAs, and their differential expression during the growth curve of S. clavuligerus for clavulanic acid production was established. The interactome of these differentially expressed (DE) RNAs displayed the sRNAs as global regulators, as they can have multiple mRNA targets. Functional annotation of the target genes of DE sRNAs demonstrated that they are directly involved in secondary metabolite production, as this was one of the most enriched categories in KEGG and COG annotations. Specifically, two sRNA have the genes of the biosynthetic gene cluster of CA as targets. Thus, these molecules add an additional layer to the regulatory cascade for CA biosynthesis, and we propose them as targets for metabolic engineering to increase CA production.